Examining motivational profiles in the dark personality tetrad using an approach-avoidance conflict task - Luke B. J. Regehr; Douglas A. Williams; Erin E. Buckels (PLoS ONE, 2025)
The present studies evaluated motives associated with the Dark Tetrad traits (Machiavellianism, narcissism, psychopathy, and sadism) using a computerized approach-avoidance conflict task (AACT). Study 1 used an Emoticon AACT with a forced choice between smiley and frowny face icons. In Phase 1, participants (n = 197) were shown a positive image if they chose to move a stick-figure manikin toward the smiley icon, and were shown a negative image if they chose the frowny icon. In Phase 2, they were offered a varying number of points (0, 1, 5, 25, or 50) for choosing the frowny icon. We found that sadism, Machiavellianism, and psychopathy were associated with accepting fewer points to approach the frowny icon that cued a negative image. This same pattern manifested for participants with low empathy levels, particularly when affective resonance was low and affective dissonance was high. Study 2 (n = 191) used an Image AACT where the choice alternatives were positive and negative images, which produced smiley or frowny icons, respectively. Sadism and dissonant emotional tendencies predicted choices directed toward negative images in Phase 2. In Studies 3 (n = 288) and 4 (n = 276), we confirmed our Emoticon AACT findings using gender-balanced samples. Studies 3 and 4 also introduced a viewing-time task (VTT). Sadism and dissonant emotional tendencies predicted decreased viewing times for positive images, but did not predict increased viewing times for negative images, suggesting that negative emotional reactions produced by the positive images were the primary motivating factor in the present AACT. Overall, our findings serve as further evidence of the different motives underlying socially aversive tendencies.